2023
DOI: 10.1002/mar.21813
|View full text |Cite
|
Sign up to set email alerts
|

I, chatbot! the impact of anthropomorphism and gaze direction on willingness to disclose personal information and behavioral intentions

Abstract: The present research focuses on the interplay between two common features of the customer service chatbot experience: gaze direction and anthropomorphism. Although the dominant approach in marketing theory and practice is to make chatbots as human‐like as possible, the current study, built on the humanness‐value‐loyalty model, addresses the chain of effects through which chatbots' nonverbal behaviors affect customers' willingness to disclose personal information and purchase intentions. By means of two experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 124 publications
0
17
0
Order By: Relevance
“…Second, there has been controversy about the effect of chatbot anthropomorphism on consumer attitudes and the results of this research show that, based on anthropomorphism theory, chatbot anthropomorphism has a positive contribution to consumer attitudes (Lei et al. , 2021; Pizzi et al. , 2023), whereas the uncanny valley theory (Mori, 1970) is not significant.…”
Section: Conclusion and Discussionmentioning
confidence: 73%
“…Second, there has been controversy about the effect of chatbot anthropomorphism on consumer attitudes and the results of this research show that, based on anthropomorphism theory, chatbot anthropomorphism has a positive contribution to consumer attitudes (Lei et al. , 2021; Pizzi et al. , 2023), whereas the uncanny valley theory (Mori, 1970) is not significant.…”
Section: Conclusion and Discussionmentioning
confidence: 73%
“…Pizzi et al (2023) found that warmth and competence can significantly mediate the relationship between anthropomorphism and gaze direction and future intentions with chatbots. These research results support the earlier findings of Pizzi et al (2023).…”
Section: Discussion On the Study 1 Resultsmentioning
confidence: 94%
“…Prior research has explained that competence can indirectly influence rational thinking and generate positive outcomes (Todd & Gigerenzer, 2003). Pizzi et al (2023) found that warmth and competence can significantly mediate the relationship between anthropomorphism and gaze direction and future intentions with chatbots. These research results support the earlier findings of Pizzi et al (2023).…”
Section: Discussion On the Study 1 Resultsmentioning
confidence: 99%
“…Brand credibility has been overlooked in the anthropomorphism literature and the link between brand credibility and chatbot characteristics has not been yet explored. Previous research in AI and chatbots have mostly found that AI/chatbot anthropomorphism has a positive influence on perceptions of competence (e.g., Pizzi et al, 2023) and warmth (e.g., S. Y. Kim et al, 2019; Pizzi et al, 2023). However, it should be noted that the relationship between anthropomorphism and perceived competence/authenticity is not always be linear or universal.…”
Section: Discussionmentioning
confidence: 99%
“…While some research has looked at how chatbots resemble human language, more research is needed to determine how different language styles affect customer perception of chatbot's humanlikeness which may lead to different perceived competence and authenticity (S. Y. Kim et al, 2019; Pizzi et al, 2023). Additionally, the effort to anthropomorphize chatbots faces the difficulty that consumers find it increasingly challenging to correctly distinguish humans from chatbots (Pizzi et al, 2023). A chatbot is the representative of a brand when interacting with customers.…”
Section: Introductionmentioning
confidence: 99%